MIGRATION AND SECURITY: MIGRATION AND SECURITY - Metodieva, Tsvetelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The history of mankind is inextricably linked to the migration of huge masses of people from their native places to other territories. Migration is a set of different in nature territorial displacements of the population, which lead to a change of residence. Despite the constraints posed by the COVID-19 pandemic, migrants continue to make secret journeys, fleeing war, violence and poverty.